KEBIJAKAN PEMBINAAN USAHA KECIL DAN MENENGAH DI KOTAMADYA JAKARTA TIMUR - Agus Jamaludin (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
This research in Sub Cooperatives and SMEs in East Jakarta for 3 weeks. This study uses field reserch and library reserch. This study by exposing the facts existing at the sub-department of Cooperatives and SMEs municipality Jaktim. This paper uses one variable, descriptive data so it does not need to use statistical parameters, whose mother only explain the data. Usefulness to determine the policy of the local government in the East Jakarta Municipality development of SMEs in East Jakarta. The theory used most of by Law number 20 of 2008 concerning the business, micro, small and medium enterprises. Small businesses that are productive economic endeavors individual or business entity that is not a subsidiary or branch company perusaahaan. While medium-sized enterprises that are productive economic enterprises stand-alone committed individual or business entity that is not a subsidiary or branch of a company that has a wealth of between Rp 500.000.000, - up to 10 millyar. The results of his research is that thanks to the policy in the development of SMEs in East Jakarta's SMEs grow and grow each year as a sign of revival of the economy. Policy development of SMEs in the area of ​​East Jakarta Municipality has implemented them on capital strengthening, hold exhibitions, folk market, enhance the entrepreneurial spirit and others. Keywords: Development of SMEs